Nursing and public policies to reduce maternal mortality in Morelos, Mexico / Enfermagem e políticas públicas para reduzir a mortalidade materna em Morelos, Mèxic - Alemán-Escobar, María de Lourdes; Pelcastre-Villafuerte, Blanca Estela; Rueda-Neria, Celina Magally (Journal of Nursing and Health, 2020)
Objectives: to identify the public policy mechanisms for reducing maternal mortality and to analyze the participation of nursing personnel in such mechanisms. Method: qualitative study, for the data collection semi-structured interviews were carried out with the administrative staff, nurses from public health services and pregnant women in Mexico. The interviews were audio-recorded, transcribed, and thematically analyzed. Results: the public policy mechanisms designed to reduce maternal mortality in Morelos include the national “Even Start in Life” program, prenatal care delivered by nursing professionals, and basic information regarding maternal mortality delivered to women, to reduce the maternal mortality. The primary challenges to properly delivering these services include a general lack of coordination between relevant committees and stakeholder, and barriers that women face accessing care. Conclusions: there are very limited actions in the design of public policies for reducing maternal mortality led by nursing personnel.